1999
DOI: 10.1099/13500872-145-1-177
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus expresses a cell surface protein that binds both IgG and β2-glycoprotein I

Abstract: The existence of a second IgG-binding protein, protein Sbi, in Staphy/ococcus aureus has been reported previously. Later data indicated that protein Sbi also bound another serum component. This component has now been affinitypurified on immobilized protein Sbi and identified as P,-glycoprotein I (/?,-GPI), also known as apolipoprotein H. The minimal P,-GPI-binding domain was identified by shotgun phage display and the binding was shown to be mediated by a region of 57 amino acids, clearly separated from the Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 25 publications
0
42
0
1
Order By: Relevance
“…(1 and 2) are homologous to the IgBDs of SpA (48). Domains 3 and 4 associate with complement components C3 and factor H, and the C-terminal domain has been proposed to retain some secreted Sbi molecules in the staphylococcal envelope by binding to lipoteichoic acids (6,44).…”
Section: Resultsmentioning
confidence: 99%
“…(1 and 2) are homologous to the IgBDs of SpA (48). Domains 3 and 4 associate with complement components C3 and factor H, and the C-terminal domain has been proposed to retain some secreted Sbi molecules in the staphylococcal envelope by binding to lipoteichoic acids (6,44).…”
Section: Resultsmentioning
confidence: 99%
“…Although the incidence and clinical significance of β2GPI-dependent aCL Ab's and anti-β2GPI Ab's in infectious diseases remains largely unknown, it is possible that infections might trigger the development of pathogenic anti-β2GPI Ab's, conceivably by molecular mimicry, and thus promote the development of APS, particularly in predisposed individuals. Recently, employing the shotgun phage display technique, Zhang et al (34) identified a Staphylococcus aureus protein, Sbi, which binds β2GPI and serves as target molecule for IgG binding. It was also shown that protein Sbi, and thus the β2GPI-binding potential, is expressed on the staphylococcal cell surface at levels varying between strains (34).…”
Section: Discussionmentioning
confidence: 99%
“…Phage display studies of S. aureus strain 8325-4 genomic DNA revealed a novel Ig-binding peptide that was later found to be part of Sbi (second binding protein of immunoglobulin) (46,47). At its N terminus are two IgG-binding domains (D1 and D2 [D1D2]) with sequence similarity to the IgG-binding domains of Spa (Fig.…”
mentioning
confidence: 99%